2010
DOI: 10.1161/circinterventions.109.912022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Introducer Sheath Coating on Endothelial Function in Humans After Transradial Coronary Procedures

Abstract: Background-The aim of this study was to compare the impact of transradial catheterization with hydrophilic-coated catheter sheaths versus uncoated sheaths on NO-mediated endothelial-dependent and -independent vasodilator function. Methods and Results-Thirty-five subjects undergoing transradial catheterization were recruited and assessed before and the day after catheterization. A subgroup was also assessed 3 to 4 months after catheterization. Subjects received hydrophilic-coated sheaths (nϭ15) or uncoated shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 51 publications
(50 reference statements)
7
33
0
1
Order By: Relevance
“…In support of this persisting deficiency in vasomotor function over time, Buturak and colleagues 32 found both FMD and NMD to be significantly reduced from baseline at 6 months post-TR procedure. In contrast, although Dawson et al 29 also reported an early impairment in FMD and NMD following RA-CA, these authors found that endothelial and smooth muscle vaso- …”
Section: Impact On Vasomotor Functionmentioning
confidence: 84%
See 1 more Smart Citation
“…In support of this persisting deficiency in vasomotor function over time, Buturak and colleagues 32 found both FMD and NMD to be significantly reduced from baseline at 6 months post-TR procedure. In contrast, although Dawson et al 29 also reported an early impairment in FMD and NMD following RA-CA, these authors found that endothelial and smooth muscle vaso- …”
Section: Impact On Vasomotor Functionmentioning
confidence: 84%
“…The duration of this damage, however, is less clear; although a number of studies have demonstrated recovery of the RA with time, 29,36 others have shown a progressive deterioration in function. 28,30 Additional studies investigating the long-term impact of TR procedures on RA function are therefore warranted.…”
Section: Commentsmentioning
confidence: 99%
“…7 After assessment and analysis of the L-FMC and FMD data, L-FMC+FMD was calculated as the sum of L-FMC and FMD. We have previously reported the impact of radial catheterization on FMD in patients included in study 1,6,7 who are nonetheless included here to assess the impact of catheterization on L-FMC and combined L-FMC+FMD.…”
Section: Fmd L-fmc+fmdmentioning
confidence: 99%
“…Due to the relatively small diameter of this artery, catheter sheath insertion is associated with endothelial denudation and impairment in endotheliumdependent FMD. [6][7][8][9] Although previous studies have assumed that L-FMC of the radial artery is endothelium-mediated, none, to our knowledge, has examined whether radial artery L-FMC is directly affected by arterial catheterization.…”
mentioning
confidence: 99%
“…However, while these coatings have proven effective at reducing the incidence of spasm and improving patient comfort, the use of hydrophilic sheaths does not appear to prevent the reduction in flow mediated dilation, an index of endothelial dysfunction [9], and did not markedly influence the incidence of radial occlusion [10,11]. Further, the use of certain hydrophilic coatings (for example, those manufactured by Cook [12,13]) has been associated with the formation of sterile granulomas and abscesses [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%